2019
DOI: 10.2218/gtopdb/f78/2019.4
|View full text |Cite
|
Sign up to set email alerts
|

Transient Receptor Potential channels (version 2019.4) in the IUPHAR/BPS Guide to Pharmacology Database

Abstract: The TRP superfamily of channels (nomenclature as agreed by NC-IUPHAR [145, 915]), whose founder member is the Drosophila Trp channel, exists in mammals as six families; TRPC, TRPM, TRPV, TRPA, TRPP and TRPML based on amino acid homologies. TRP subunits contain six putative transmembrane domains and assemble as homo- or hetero-tetramers to form cation selective channels with diverse modes of activation and varied permeation properties (reviewed by [630]). Established, or potential, physiological functions of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 835 publications
2
11
0
Order By: Relevance
“…It is well known that CaMKIIα activation requires elevated intracellular Ca 2+ and activated calmodulin. TRPC1/4/5 channels belong to nonselective calcium‐permeable cation channels 7,8 . In the present study, we found that application of DAMGO induced a dramatic Ca 2+ elevation in spinal dorsal horn neurons, which is dependent on the activity of TRPC1/4/5 channels.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…It is well known that CaMKIIα activation requires elevated intracellular Ca 2+ and activated calmodulin. TRPC1/4/5 channels belong to nonselective calcium‐permeable cation channels 7,8 . In the present study, we found that application of DAMGO induced a dramatic Ca 2+ elevation in spinal dorsal horn neurons, which is dependent on the activity of TRPC1/4/5 channels.…”
Section: Discussionsupporting
confidence: 60%
“…Previous studies have shown that opioid withdrawal induces postsynaptic Ca 2+ accumulation, which are assumed to underlie opioid withdrawal‐induced LTP 4 . Since canonical transient receptor potential channels (TRPC channels) are known to be Ca 2+ permeable, 7‐9 enhanced Ca 2+ influx via TRPC1/4/5 channels may account for the requirement of TRPC1/4/5 channels for opioid withdrawal‐induced LTP. We examined this possibility by direct measurement of Ca 2+ changes in excitatory spinal dorsal horn neurons, using Ca 2+ sensor GCaMP6s specifically expressed in excitatory spinal dorsal horn neurons 35,36 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Most studies of CCE are based on the use of gene knockout or pharmacological tools to block or activate TRP/Orai channels [17,18]. However, cells often adapt to calcium channel gene invalidation by reorganizing their calcium homeostasome to maintain calcium homeostasis.…”
Section: Introductionmentioning
confidence: 99%
“…The 50 finely tuned control of these entries is therefore essential for the differential modulation of cancer cell studies but seems to be a common mechanism in many cell types (Kim et al, pathophysiological cellular processes is currently hampered however by the limited number 78 of molecular tools and experimental approaches available to specifically modulate CCE. 79 Most studies of CCE are based on the use of gene knockout or pharmacological tools 80 to block or activate TRP/ORAI channels (Hu et al, 2004;Blair et al, 2019). However, cells 81 often adapt to calcium channel gene invalidation by reorganizing their calcium 82 homeostasome to maintain calcium homeostasis.…”
Section: Introduction 42mentioning
confidence: 99%